Understanding Gender Power Relations and Emotions of Rohingya Adolescent Girls in Bangladesh - Ahmed, Nashida (Journal of Gender and Power, 2023)
This paper sheds light on the intertwined aspects of gender, power, and emotion by exploring the lived experiences of Rohingya adolescent girls who are at risk of GBV which is widespread in camp settings. Narrative interviews and focus group discussions offered opportunities to twenty-five unmarried and married adolescent girls to talk about gender-based discrimination and violence in everyday household and community practices that reconstruct gender and power dynamics and shape girls’ emotions. Drawn from the elements of the three domains of power (Mcdonald, 1980), the paper shows that the prevailing sexist practices in Rohingya society divide “girls” and “boys” into two different categories and create conditions for subordination of girls on the basis of sex-based irrational differentiation. Such power capability rooted in the contexts of power bases put boys as a group in the position to use power in extreme form as violence and successful power use underlies power outcomes. Importantly, negative emotions such as sadness, fear, anger, guilt, and disgust interact with these three domains of power. Projects that define power as empowerment would be supportive for girls’ empowerment and experience of positive emotions.